Guest Editorial Advancing Biomedical Discovery and Healthcare Delivery Through Digital Technology - Cerutti, Sergio; Eskofier, Björn; Tourassi, Georgia (IEEE Journal of Biomedical and Health Informatics, 2023)
Digital technology has had a significant impact on biomedical sciences and healthcare delivery, not only in terms of theoretical and practical contributions to involved disciplines but also due to the profound and rapid changes in medical research and in medical care applications, as well as in the management organization after the recent COVID-19 epidemic. In this regard, several elements stand out from the 11 selected contributions published in this Special Issue.
CRIS-Team Scopus Importer:2023-06-30